(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article investigates the effects of modified dispersed and fibrous fillers on the mechanical and operational properties of sulfur-based concrete, as well as determines the optimal time and method of modification. The obtained results were compared with the M450 grade heavy concrete currently used in the production of reinforced concrete sleepers for railway transport